1997
DOI: 10.1046/j.1525-1497.1997.12109.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Role Models on Medical Students

Abstract: OBJECTIVE:To explore the relationship between exposure to clinical role models during medical school and the students' choice of clinical field for residency training, and to estimate the strength of this association. DESIGN:Cross-section study. SETTING:McGill University School of Medicine, Montreal, Canada. PARTICIPANTS:Of the 146 graduating medical students in the class of 1995, 136 participated. MEASUREMENTS AND MAIN RESULTS:Clinical field chosen by students for residency training and the students' assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
131
0
5

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(145 citation statements)
references
References 13 publications
(10 reference statements)
6
131
0
5
Order By: Relevance
“…[9][10][11] However, many faculty physicians trained in a culture that did not place as much emphasis on reducing unnecessary costs of care; therefore, they must adapt their own teaching methods and practice patterns to better influence trainees to be good stewards of health care resources. 12,13 Given the significant impact of faculty behavior on resident practice patterns, [9][10][11] it is of vital importance to understand whether faculty are appropriately role-modeling cost-conscious care.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] However, many faculty physicians trained in a culture that did not place as much emphasis on reducing unnecessary costs of care; therefore, they must adapt their own teaching methods and practice patterns to better influence trainees to be good stewards of health care resources. 12,13 Given the significant impact of faculty behavior on resident practice patterns, [9][10][11] it is of vital importance to understand whether faculty are appropriately role-modeling cost-conscious care.…”
Section: Introductionmentioning
confidence: 99%
“…12 Role models can have a powerful effect on students and residents in training. Wright et al 13 found that interaction with a "sufficient" role model influenced career choice. Another study of physician executives found that most felt more comfortable with the label of "role model" rather than "mentor" when describing people who influenced their careers 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Issues for Women and Minorities. As Wright 1 and others 2,3 have shown, female students preferentially choose female role models. In one study, 2 female graduate students who identified female professors as role models described themselves as more confident and reported increased satisfaction with the student role when compared with female students who had male role models.…”
mentioning
confidence: 81%